Analysis of Appointment Agreements in the Context of Illegal Land Transfers to Foreign Nationals - Aslan Noor; Adinda Amalia Putri; Tubagus Langlang Buana; Tuti Zulaeha; Jefri Situmorang; Dafina Nurulita Suherman; Rizki Daffa A (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
The issue of nominee agreements in Indonesia poses challenges in balancing the promotion of foreign investment with the protection of land sovereignty. Despite strict legal prohibitions, this practice continues to flourish and creates uncertainty in legal doctrine and agrarian governance. This study aims to analyse the legal status of nominee agreements under Indonesian positive law, particularly in the context of Law No. 25 of 2007 on Investment (UUPM), and to evaluate the legal consequences of land ownership by foreign investors through this mechanism. This study uses a normative juridical approach, referring to primary legal sources such as the UUPM, the 1960 Basic Agrarian Law (UUPA), and the 2007 Limited Liability Company Law (UUPT), as well as secondary and tertiary literature. The results of the study show that nominee agreements are prohibited in the context of corporations based on the UUPM and UUPT, and are therefore null and void from the outset. However, the absence of specific regulations on land ownership creates a legal vacuum that allows this practice to continue. Nominee agreements fulfil the subjective elements of an agreement but fail to fulfil the legal causes according to the Civil Code, making them legally invalid but still operating in practice. This poses legal and social risks for foreign investors and local nominees and has an impact on agrarian justice and the credibility of the national investment system. This study emphasises the importance of regulatory harmonisation and consistent law enforcement to strengthen legal certainty and maintain state sovereignty over land in accordance with Indonesia's constitutional mandate.